1998
DOI: 10.1128/jvi.72.3.1782-1789.1998
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Assembly Function of the Human Immunodeficiency Virus Type 1 Gag Protein Nucleocapsid Domain

Abstract: Previous studies have shown that in addition to its function in specific RNA encapsidation, the human immunodeficiency virus type 1 (HIV-1) nucleocapsid (NC) is required for efficient virus particle assembly. However, the mechanism by which NC facilitates the assembly process is not clearly established. Formally, NC could act by constraining the Pr55 gag polyprotein into an assembly-competent conformation or by masking residues which block the assembly process. Alternati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
72
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(77 citation statements)
references
References 41 publications
(112 reference statements)
5
72
0
Order By: Relevance
“…While we did not specifically measure the viral genomic content of each mutant, results from this (Fig. 6) and previous studies (Johnson et al, 2002;Zhang et al, 1998) indicate that VLP assembly can be restored to near-wt levels when a leucine zipper motif is inserted into the deleted NC region, thus suggesting that viral genomic RNA is at least partly dispensable for VLP assembly. However, NC(ZIP) efficiency in VLP production was significantly reduced and RNA packaging capacity concomitantly reduced when MA was removed (ΔMA/NC [ZIP]).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…While we did not specifically measure the viral genomic content of each mutant, results from this (Fig. 6) and previous studies (Johnson et al, 2002;Zhang et al, 1998) indicate that VLP assembly can be restored to near-wt levels when a leucine zipper motif is inserted into the deleted NC region, thus suggesting that viral genomic RNA is at least partly dispensable for VLP assembly. However, NC(ZIP) efficiency in VLP production was significantly reduced and RNA packaging capacity concomitantly reduced when MA was removed (ΔMA/NC [ZIP]).…”
Section: Discussionmentioning
confidence: 70%
“…Besides contributing to Gag multimerization, HIV-1 NC is thought to play a key role in mediating viral RNA packaging (Berkowitz et al, 1995;Cimarelli et al, 2000;Gorelick et al, 1993;Poon et al, 1996). However, NC-dependent RNA incorporation is not essential for retrovirus assembly, since a foreign protein sequence or leucine zipper motif that does not associate with RNA can serve as NC substitutes to restore VLP production to wt levels (Johnson et al, 2002;Zhang et al, 1998). Furthermore, the neutralization of the highly positive NC charge by substitute mutations results in significant reductions of virus-associated RNA with no major effects on HIV-1 assembly and budding (Wang and Aldovini, 2002;Wang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to playing a key role in viral RNA packaging (Berkowitz et al, 1993(Berkowitz et al, , 1995Poon et al, 1996;Zhang and Barklis, 1997), NC contains an I domain that is responsible for Gag-Gag interactions (Bennett et al, 1993;Bowzard et al, 1998). Heterologous polypeptides capable of self-association have been shown to confer the ability to efficiently produce chimeric VLPs when substituted for HIV-1 NC (Accola et al, 2000;Burniston et al, 1999;Johnson et al, 2002;Zhang et al, 1998). However, replacing NC with a leucine-zipper motif that does not encapsidate RNA abolishes hA3G packaging without significantly affecting HIV-1 virion production (Zennou et al, 2004), suggesting RNA involvement in hA3G incorporation.…”
Section: Introductionmentioning
confidence: 99%
“…Plasmid DNAs containing wt (wtZiP) and mutant (KZiP) leucine zipper domains of human CREB [24] were kindly provided by E. Barklis [54]. cDNA fragments of the wt and mutant leucine zipper domains were PCR-amplified, digested, and ligated into DNC, yielding the respective constructs DNC(wtZiP) and DNC(KZiP).…”
Section: Plasmid Constructionmentioning
confidence: 99%
“…Likewise, recombinant SARS-CoV nucleocapsid proteins can undergo multimerization via self-association [16,30,42,51]. Since heterologous polypeptides that form interprotein contacts permit efficient VLP production when placed in the HIV-1 NC region [1,9,20,54], we initially tested whether SARS-CoV N substitution for HIV-1 NC supports chimeric VLP assembly and release, and found that HIV-1 Gag mutants containing SARS-CoV N coding sequences as NC substitutes are capable of VLP assembly. This suggests that the HIV-1 NC assembly domain can be functionally replaced with the SARS-CoV N.…”
Section: Introductionmentioning
confidence: 99%